The Economics of Crime: Investigating the Drugs-Crime Channel. Empirical Evidence from Panel Data of the German States - Horst Entorf; Peter Winkler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The rising trends both in drug addiction and crime rates are of major public concern in Germany. Surprisingly, the economic theory of crime seems to ignore the drugs-crime nexus, whereas the criminological literature considers illicit drug use a main reason of criminal activities. This paper provides an econometric assessment of the drugs-crime channel within a Becker-Ehrlich model of crime supply. We analyse three different channels from drug abuse to crime: system-related, economic-related and pharmacological effects. Estimation with panel data from the German states allows us to take into account further factors that might influence both drug abuse and crime. The results indicate that drug offences have a significant impact, in particular on property crimes. We attribute this to a strong economic-related channel of drug abuse on crime.
Keywords: J49; K42; I19; C23; 330; Drogenkonsum; Kriminalität; Kriminalitätsökonomik; Schätzung; Deutschland